Moderating Effect of Firm Size on Financial Uncertainty Indicators and Financial Performance of Manufacturing Firms in Kenya - Jane Pila; Willy Muturi; Tobias Olweny (Journal of Accounting and Finance in Emerging Economies, 2022)
Purpose: To what extend does firm size moderates’ relationship between manufacturing firms’ financial performance and financial uncertainty indicators. This was necessitated below expectation performance of manufacturing firms in Kenya. They are expected to employ 30% of Kenya population, contribute to Gross domestic product up to 10% and attract at least 10% of large investor. This has not been possible in the last 12 years.